Fungal reservoirs in the hospital environment: prevalence and factors associated with Aspergillus contamination of bed rails in a tertiary hospital in Nigeria - Makanjuola, Olufunmilola; Igbor, Gloria; Bamigbola, Florence (International Journal of Infection Control, 2026)
Background: Aspergillus species are common environmental fungi known to cause Aspergillosis, often presenting as an invasive infection in individuals with a compromised immune system. It is transmitted by the inhalation of Aspergillus spores and contributes to healthcare associated infections in hospitalised patients. Since these patients spend most of the day in their hospital beds, the presence of Aspergillus spores in such settings puts the patient at risk of inhaling aerosolised spores leading to infections. Objective: To determine the prevalence, distribution, and factors associated with Aspergillus contamination of hospital bed rails. Design: This laboratory-based cross-sectional study was carried out at the University College Hospital, Ibadan, Southwest Nigeria, between May and June 2023. In all, 100 beds which were occupied by patients in 13 wards were included in this study. The left and right rails of beds were swabbed and processed for the detection of Aspergillus species using fungal culture and microscopy. A checklist was used to assess selected infection prevention and control measures in the wards. Results: The total number of bedrails with Aspergillus isolated across all the wards where samples were taken was 56 (28.0%). Aspergillus niger was the most prevalent specie (64.2%) followed by Aspergillus flavus (30.4%), then Aspergillus fumigatus (5.4%). The prevalence of Aspergillus contamination was related to the level of sanitation and proximity to construction activity. Conclusion: To reduce the risk of Aspergillus infections in hospitalised patients, adequate infection prevention and control measures including thorough cleaning and disinfection should be strictly adhered to.